Myth as a Means of Ordering and Organizing Social Reality - Baklanov, Igor S.; Baklanova, Olga A.; Erokhin, Alexey M.; Ponarina, Natalia N.; Akopyan, Goarik A. (Journal of History Culture and Art Research, 2018)
This study investigates the phenomenon of social myth as a factor of forming and transforming the consciousness of social actors. It is defined that one of the factors of appealing to mythological representation of reality is the crisis of scientific orientations of modernism. In this plane, the article studies phenomenological receptions of myth as well as the process of mythologization of modern social reality. Moreover, attention is drawn to the fact that mythologization fixes an idea of social reality and its axiological (value) dimension in the consciousness of separate individuals and their groups. Myths are axiological indicators; the more controversial society values are the greater number of myths is produced by social consciousness to eliminate these contradictions. The difference between modern and archaic myth has both qualitative and quantitative aspects. Modern society generates a great number of myths with much more narrow content. This is a consequence of "specialization" of myths, their orientation towards solving particular local tasks: political, economic, etc. Functional and structural changes of social myths can be accounted for by critical, permanently transitional condition of society in which myth compensates the unformed elements of new social practices. However, the content side of myth is not a crisis but social request and values of particular culture. The question about the necessity to fight against myths probably should be answered negatively if we don’t mean the most dangerous myths posing a serious threat for society. Myths are in harmony with social consciousness and arise in places where there is a fault between current and desirable normativity. Thus, when social practices become stable social consciousness itself displaces and nullifies myths that are responsible for harmonization of new order and they become demanded.